2002
DOI: 10.1002/ps.523
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro metabolism of fipronil by larvae of the European corn borer Ostrinia nubilalis

Abstract: In vivo and in vitro metabolism of [14C]fipronil was examined in a susceptible European corn borer (Ostrinia nubilalis, Hübner) laboratory strain. [14C]Fipronil penetrated the larval integument slowly, with 71.5% of the applied radioactivity recovered from surface rinses 24 h after topical application. Despite this slow penetration, radioactivity was detected in both the excrement and internal organo-soluble fractions. Radioactivity in the internal aqueous fraction and tissue pellet accounted for less than 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Fipronil is biotransformed by microsomal monooxygenases to a number of metabolites, the most important of which is fipronil‐sulfone, but most insects are susceptible to both the fipronil parent and the metabolite. Durham et al 48 showed that, in the European corn borer Ostrinia nubilalis (Hübner), the synergist PBO inhibited the activity of the microsomal monooxygenases and so suppressed the biotransformation process. This had no overall effect on the PBO synergism of fipronil against O. nubilalis , as both the parent and metabolite molecules were highly toxic to that insect, but the authors pointed out that small differences between the activity of the two compounds against other insects could lead to the observed variations in PBO synergism mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Fipronil is biotransformed by microsomal monooxygenases to a number of metabolites, the most important of which is fipronil‐sulfone, but most insects are susceptible to both the fipronil parent and the metabolite. Durham et al 48 showed that, in the European corn borer Ostrinia nubilalis (Hübner), the synergist PBO inhibited the activity of the microsomal monooxygenases and so suppressed the biotransformation process. This had no overall effect on the PBO synergism of fipronil against O. nubilalis , as both the parent and metabolite molecules were highly toxic to that insect, but the authors pointed out that small differences between the activity of the two compounds against other insects could lead to the observed variations in PBO synergism mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The microsomal monooxygenase oxidative system is considered to be involved in the degradation of fipronil, as the formation of fipronil-sulfone, the predominant metabolite of fipronil, is dependent on this enzyme system (Brookhart et al 1994; Scharf et al 2000; Durham et al 2002). A synergistic action would indicate the potential for using piperonyl butoxide to decrease the toxicity of fipronil that can be metabolised by P450 oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic action would indicate the potential for using piperonyl butoxide to decrease the toxicity of fipronil that can be metabolised by P450 oxidative metabolism. It is interesting that the effect of piperonyl butoxide on the action of fipronil was synergistic in house flies ( Musca domestica ) (Scott et al 1997), antagonistic in German cockroach ( Blattella germanica ) and European corn borer ( Ostrinia nubilalis ) (Durham et al 2002; Valles et al 1997), and had no effect in western corn rootworm ( Diabrotica virgifera virgifera ) (Scharfet al 1999). In this paper, the application of PBO had a significant antagonistic effect on the toxicity of fipronil accompanied with decreasing the effects of fipronil on mortality of the susceptible larvae, whereas PBO had an obvious synergistic effect on the toxicity of fipronil to the resistant larvae causing a decreased LD 50 value and an increased mortality compared to fipronil alone.…”
Section: Discussionmentioning
confidence: 99%
“…with fipronil (Caboni et al, 2003). In European corn borer (Ostrinia nubilalis Hubner), fipronil sulfone was formed through the microsomal cytochrome P450 oxidation system in the midgut in vivo and in vitro (Durham et al, 2002). The biological conversion of fipronil to fipronil sulfone was completely blocked with piperonyl butoxide, a cytochrome P450 monooxygenase inhibitor, in vivo and in vitro (Hainzl et al, 1998;Caboni et al, 2003).…”
mentioning
confidence: 99%